Effects of Exercise Intensity on Flow Mediated Dilation in Healthy Humans - Birk, G. K.; Dawson, E. A.; Batterham, A. M.; Atkinson, G.; Cable, T.; Thijssen, D.H. J.; Green, D. J. (International Journal of Sports Medicine, 2013)
Previous studies have demonstrated conflicting results on the effects of acute exercise on FMD. The aim of the study was to examine brachial artery FMD before and after 3 bouts of acute exercise performed at different intensities. 10 healthy males (mean±SD age: 22±1 years) completed 30 min of cycling at 50, 70 and 85% maximal heart rate (HRmax). Brachial artery FMD and the shear rate area-under-the-curve (cuff deflation to peak dilation; SRAUC) were assessed pre- and immediately post-exercise using high-resolution echo-Doppler. A generalized estimating equation (GEE) analysis was used to estimate the effect magnitudes of exercise intensity and time (pre/post) on FMD, whilst controlling for the influence of baseline diameter and SRAUC. Both baseline diameter and SRAUC were elevated by exercise. With covariate-control of these variables, the decrease in brachial artery FMD was negligible after exercise at 50% HRmax (6.3±2.6 vs. 5.9±2.5%; 95%CI for difference:  − 0.59–1.34%) with larger decreases in FMD after exercise at 70% (6.1±1.8 vs. 4.7±1.9%; 95%CI for difference: 0.08–2.58%) and at 85% HRmax (6.6±1.6 vs. 3.6±2.2%; 95%CI: 0.41–5.42%). In conclusion, even after accounting for exercise-mediated changes in shear and baseline diameter, our data indicate that a negative relationship exists between exercise intensity and FMD.
Keywords: baseline diameter; cycling; FMD; shear rate